Overview of Community Tourism Awareness in Tlangoh Beach, Bangkalan - Rosyidah, Rezkiyah; Astuti, Jayaning Sila; Arnani, Ni Putu Rizky (Universitas Muhammadiyah Sidoarjo, 2024)
Bangkalan has a number of areas that have the potential to be developed as tourism objects. Even though it has quite a lot of tourist attractions, these various tourist attractions are less known to the people of East Java. The absence of good management or a change in the community's mindset to become a tourism-aware community is the cause of the lack of optimal tourism development in Bangkalan. The aim of this research is to describe tourism awareness of the people in Tlangoh Beach - Bangkalan. This research adopts a descriptive study. The population consists of people around Tlangoh Beach - Bangkalan. The sample, comprising 36 individuals was selected using a purposive sampling technique. Research data was collected through a questionnaire designed to measure tourism awareness was adapted from an instrument compiled by Setyaningsih, et al (2021) with 28 aitem and score of reliability is 0.935. The data analysis used in this research is a descriptive test was used with the help of the SPSS application. Based on the hypothesis testing find that people in Tlangoh Beach – Bangkalan have tourism awareness in the medium category. It means that the people in Tlangoh Beach – Bangkalan is quite capable to implementing the elements of Sapta Pesona, which is safe, orderly, clean, cool, beautiful, friendly and memorable, in effort to develop tourism at Tlangoh Beach - Bangkalan. Highlights: Moderate Tourism Awareness: Most people in Tlangoh Beach have medium awareness of tourism development. Cleanliness Emphasis: The community focuses more on maintaining cleanliness to enhance the tourist experience. Lack of Uniqueness: The local culture and unique souvenirs are underutilized, limiting the potential for memorable tourist experiences. Keywords: Community-Based Tourism, Tourism Awareness, Tourism Development